Quantifying Gaze Behavior During Real-World Interactions Using Automated Object, Face, and Fixation Detection - Chukoskie, Leanne; Guo, Shengyao; Ho, Eric; Zheng, Yalun; Chen, Qiming; Meng, Vivian; Cao, John; Devgan, Nikhita; Wu, Si; Cosman, Pamela C. (IEEE transactions on cognitive and developmental systems, 2018)
As technologies develop for acquiring gaze behavior in real world social settings, robust methods are needed that minimize the time required for a trained observer to code behaviors. We record gaze behavior from a subject wearing eye-tracking glasses during a naturalistic interaction with three other people, with multiple objects that are referred to or manipulated during the interaction. The resulting gaze-in-world video from each interaction can be manually coded for different behaviors, but this is extremely time-consuming and requires trained behavioral coders. Instead, we use a neural network to detect objects, and a Viola-Jones framework with feature tracking to detect faces. The time sequence of gazes landing within the object/face bounding boxes is processed for run lengths to determine "looks," and we discuss optimization of run length parameters. Algorithm performance is compared against an expert holistic ground truth.